2022
DOI: 10.1186/s13643-021-01874-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high-intensity interval training on blood lactate levels and cognition in healthy adults: protocol for systematic review and network meta-analyses

Abstract: Background High-intensity interval training (HIIT) has shown to confer cognitive benefits in healthy adults, via a mechanism purportedly driven by the exercise metabolite lactate. However, our understanding of the exercise parameters (e.g., work interval duration, session volume, work-to-rest ratio) that evoke a peak blood lactate response in healthy adults is limited. Moreover, evidence relating HIIT-induced blood lactate and cognitive performance has yet to be reviewed and analyzed. The prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 64 publications
0
4
1
Order By: Relevance
“…By analyzing the results related to the physiological parameters, we found a significant increase in the level of lactate starting from the first post-exercise session, and a further increase after the third one. Compared to other studies [4,38,39], the slightly high values in the PRE session can be ascribed to the presence of the warm-up session. The level of lactate after each HIFT repetition showed lower values than the ones reported in [38]; this may be due to the methodology used to acquire the level of lactate.…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…By analyzing the results related to the physiological parameters, we found a significant increase in the level of lactate starting from the first post-exercise session, and a further increase after the third one. Compared to other studies [4,38,39], the slightly high values in the PRE session can be ascribed to the presence of the warm-up session. The level of lactate after each HIFT repetition showed lower values than the ones reported in [38]; this may be due to the methodology used to acquire the level of lactate.…”
Section: Discussioncontrasting
confidence: 78%
“…In fact, by considering the trend of the statistical results, we can speculate that accuracy in the execution of cognitive tasks does not vary after the third repetition, suggesting that the necessity of six repetitions is an overestimation in regard to planning training programs. This finding could be used as a starting point to solve one of the most unanswered questions when designing training, i.e., the ideal number of circuit repetitions; in fact, Jacob et al found a strong connection between cognitive performance and the duration of an exercise program [4].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Lactate synthesized as a result of exercise is used to satisfy the energy demands of neurons 68 and, as a neuronal signaling molecule, to increase BDNF expression 69 . Therefore, HIIT programs would result in a peak accumulation of lactate in the blood, which is responsible for augmented BDNF expression in the brain 68 …”
Section: Discussionmentioning
confidence: 99%
“…65 This myokine accumulates in the blood during acute exercise depending on the intensity and duration of the exercise and is able to cross the blood-brain barrier. 66,67 Lactate synthesized as a result of exercise is used to satisfy the energy demands of neurons 68 and, as a neuronal signaling molecule, to increase BDNF expression. 69 Therefore, HIIT programs would result in a peak accumulation of lactate in the blood, which is responsible for augmented BDNF expression in the brain.…”
Section: Hiit Versus Control Conditionmentioning
confidence: 99%